2022
DOI: 10.1332/251510821x16523466058289
|View full text |Cite
|
Sign up to set email alerts
|

The digital storytelling of feminist foreign policy: Sweden’s state feminism in digital diplomacy

Abstract: This article interrogates the digital storytelling of Sweden’s feminist foreign policy. Drawing on scholarship on state feminism and digital diplomacy, it shows how digital platforms offer opportunities to reproduce narratives of state feminism through storytelling. We propose that digital diplomacy is used to advance feminist foreign policy through emotional sense-making that requires the telling of personal stories. The article provides a narrative analysis of the stories of women and girls that symbolise an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Thus, it could be seen as a response to an ongoing global human and especially women's rights crisis, understood in broader terms as a systematic subordination of women and girls. The feminist foreign policy was part of Sweden's overall branding as a feminist nation at the time (see Bergman Rosamond & Hedling, 2022) and an example of how gender-friendly norms could act as an "identity marker," describing who a country is and "how it intends to conduct itself in the world" (Lee-Koo, 2020, p. 240). Sweden thus exemplified a small country striving to make its voice heard by carving out a reputational niche (Jansen, 2008;van Ham, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it could be seen as a response to an ongoing global human and especially women's rights crisis, understood in broader terms as a systematic subordination of women and girls. The feminist foreign policy was part of Sweden's overall branding as a feminist nation at the time (see Bergman Rosamond & Hedling, 2022) and an example of how gender-friendly norms could act as an "identity marker," describing who a country is and "how it intends to conduct itself in the world" (Lee-Koo, 2020, p. 240). Sweden thus exemplified a small country striving to make its voice heard by carving out a reputational niche (Jansen, 2008;van Ham, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The use of social media for spreading government strategic policies has been studied by scholars in various countries. A study by Rosamond and Hedling (2022) highlights State feminism and digital diplomacy, exploring Sweden's feminist foreign policy by utilizing digital storytelling. This paper found that, among others, feminist foreign policy digital storytelling enables the government, in this context the Ministry for Foreign Affairs, to connect with digital audiences, by using success stories.…”
Section: Methods and Theorymentioning
confidence: 99%
“…The gradual digitalisation of diplomacy has led practices of communication and representation on social media to become expected of diplomats as part of the job. In addition to managing the emotions of others in their offline relations, diplomats must project a version of the self online, that depend on new norms of emotion-laden discourse and visual representations (Bergman Rosamond and Hedling 2022). Social media and the specific socio-political affordances they offer, have greatly contributed to the commodification of emotions in political communication (Stark, 2020).…”
Section: Introductionmentioning
confidence: 99%